TRANSITIVITY SYSTEM IN CNN ONLINE NEWS - Nurul . Qomariah; Amrin . Saragih; Sri Minda Murni (LINGUISTIK TERAPAN, 2022)
This study was concerned with the types of transitivity system elements in CNN Online News. The objectives of this descriptive qualitative study were to discover: (1) the types of transitivity system, (2) the realization of transitivity system, and (3) the reasons for transitivity system realized in CNN Online News. The data of this study were clauses that consist of a transitivity system in 10 Covid-19 Online News taken from CNN Online News. The results of the study showed that: 1) CNN Online News realized all the types of process: Material, Mental, Relational, Behavioral, Verbal, and Existential process. The dominant process was Material Process. It was realized 214 (50,47%). CNN Online News realized participants: Actor, Goal, Sayer, Carrier, Attribute, Verbiage, Senser, Phenomenon, Target, Existing, Existence, Behaver, Token, Value, Receiver, Behavior, and Range. Actor and Goal were dominantly realized in the clauses of CNN Online News, there were 167 (26,38%) of Actor and 141 (22,27%) of Goal. The most dominant was Actor, and CNN Online News realized circumstances: Location, Cause, Manner, Accompaniment, Extent, Matter, Angle, and Role. It was realized 193 (60, 50%). The dominant was Location; 2) There were congruent realization and incongruent realization of transitivity system. The most dominant realization was congruent realization; 3) The reason why the types of transitivity system realized in CNN Online News is based on the context of the situation related to the field. Field stand for three entries, namely arena/social activity [+institutionalized/-institutionalized], participant’s characteristics [person/social] and semantic domain [+specialized/-specialized]. The most dominant was arena/social activity, especially [-institutionalized]. Keywords: Metafunction, Transitivity System, Online News, CNN